2021
DOI: 10.1213/ane.0000000000005825
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Regulated Ventilator Splitting for Disaster Relief: Design, Testing, and Clinical Experience

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has revealed that even the best-resourced hospitals may lack sufficient ventilators to support patients under surge conditions. During a pandemic or mass trauma, an affordable, low-maintenance, off-the-shelf device that would allow health care teams to rapidly expand their ventilator capacity could prove lifesaving, but only if it can be safely integrated into a complex and rapidly changing clinical environment. Here, we define an approach to safe ventilator sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Raredon et al . 's[ 37 ] study showed that male nurses are more prepared in the face of disasters. The difference in the results of the studies with the present study can be caused by various factors, from the demographic characteristics of the nurses to the factors related to accidents and as mentioned earlier, such as the previous experience of the nurses and the extent of an accident.…”
Section: Discussionmentioning
confidence: 99%
“…Raredon et al . 's[ 37 ] study showed that male nurses are more prepared in the face of disasters. The difference in the results of the studies with the present study can be caused by various factors, from the demographic characteristics of the nurses to the factors related to accidents and as mentioned earlier, such as the previous experience of the nurses and the extent of an accident.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, two major groups of devices to titrate VTs in ventilator sharing were described [ 26 ]. FCV reducing the cross-sectional area with different types of valves and PGV, which uses a spring load.…”
Section: Discussionmentioning
confidence: 99%
“…Implementing this in a shared ventilator setup with pressure-controlled ventilation creates the possibility to individualize VTs. The flow resistance for PGV decreases with increasing flow and the pressure drop across the valve is independent from it [ 26 ]. The VT can therefore only be controlled by changing the pressure set by the valve or the ventilator and hence change the inspiratory pressure of the patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the contributions: a critical care primer for anesthesiologists filling in to deliver critical care, 58 describing initial clinical impressions of COVID-19 patients in March of 2020, 59 outlining effects of prone positioning, 60 developing protective barrier strategies for caregivers during airway management, 61 describing safe practices for tracheostomy 62 and the effect of cancelling elective cases on ICU capacity, 63 identifying challenges in sedation for mechanically ventilated patients, 64 and exploring the possibilities of ventilator splitting. 65 A&A ’s April 2021 observation that aspirin use was correlated with a considerably lower severity of COVID-19-related ARDS 66 was highly cited and picked up by national news organizations. 67 A&A was also fortunate to publish the remarkable, dramatic, and unprecedented stories of how 2 New York hospitals converted their ORs to ICUs during the initial Spring 2020 surge.…”
Section: Since 2010: the Blossoming Of Critical Care Researchmentioning
confidence: 99%